Keratin 19: a key role player in the invasion of human hepatocellular carcinomas. Issue 4 (19th August 2013) - Govaere, Olivier; Komuta, Mina; Berkers, Johannes; Spee, Bart; Janssen, Carl; de Luca, Francesca; Katoonizadeh, Aezam; Wouters, Jasper; van Kempen, Léon C; Durnez, Anne; Verslype, Chris; De Kock, Joery; et al.
Abstract : Objective: Keratin (K)19, a biliary/hepatic progenitor cell (HPC) marker, is expressed in a subset of hepatocellular carcinomas (HCC) with poor prognosis. The underlying mechanisms driving this phenotype of K19-positive HCC remain elusive. Design: Clinicopathological value of K19 was compared with EpCAM, and α-fetoprotein, in a Caucasian cohort of 242 consecutive patients (167 surgical specimens, 75 needle biopsies) with different underlying aetiologies. Using microarrays and microRNA profiling the molecular phenotype of K19-positive HCCs was identified. Clinical primary HCC samples were submitted to in vitro invasion assays and to side population analysis. HCC cell lines were transfected with synthetic siRNAs against KRT19 and submitted to invasion and cytotoxicity assays. Results: In the cohort of surgical specimens, K19 expression showed the strongest correlation with increased tumour size (p<0.01), decreased tumour differentiation (p<0.001), metastasis (p<0.05) and microvascular invasion (p<0.001). The prognostic value of K19 was also confirmed in a set of 75 needle biopsies. Profiling showed that K19-positive HCCs highly express invasion-related/metastasis-related markers (eg, VASP, TACSTD2, LAMB1, LAMC2, PDGFRA ), biliary/HPC markers (eg, CD133, GSTP1, NOTCH2, JAG1 ) and members of the miRNA family 200 (eg, miR-141, miR-200c). In vitro, primary human K19-positive tumour cells showed increased invasiveness, and reside in the chemoresistant side population. Functionally, K19/ KRT19 knockdown results in reduced invasion, loss of invadopodia formation and decreased resistance to doxorubicin, 5-fluorouracil and sorafenib. Conclusions: Giving the distinct invasive properties, the different molecular profile and the poor prognostic outcome, K19-positive HCCs should be considered as a seperate entity of HCCs.